Kontrol Optimal pada Model Epidemik SIR Penyakit Demam Berdarah - Katrina Pareallo; Wahidah Sanusi; Syafruddin Side (Universitas Negeri Makassar, 2018)
This study discusses about the optimal control on dengue fever distribution model using the minimum principle of Pontryagin. Dengue is a disease caused by dengue virus it transmitted by the female mosquitos species, namely Aedes aegeypti and Aedes Albopictus. Thus disease cause death if not treated seriously. The disease can be prevented by vaccine, called Chimeric Yellow Fever 17D-Tetravalent Dengue Vaccine(CYD-TDV). The discussion starts from determining the SIR model using the controls, determining the optimal control using the minimum principle of Pontryagin , the simulation using Maple software and the result analysis. In this study obtained the system of differential equations, optimal control equations, and graphs of the SIR model without using controls and using the control. Based on the results obtained concluded that by adding control factor to SIR model can minimize the number of infected individuals.